2020
DOI: 10.1080/09638199.2020.1831042
|View full text |Cite
|
Sign up to set email alerts
|

Does the designation of least developed country status promote exports?

Abstract: In this paper we examine to what extent developing countries export more as a result of having the official Least Developed Country (LDC) status. We estimate a gravity model of trade over the period 1973-2013, in which identification is achieved by exploiting the particularities and asymmetries of 'inclusion' and 'graduation' criteria of LDC status. As mechanisms through which LDCs might benefit, we evaluate the effectiveness of individual trade preference schemes for LDCs of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
(32 reference statements)
0
14
0
2
Order By: Relevance
“…Additionally, many factors can hinder the utilization of NRTPs once bene ciary countries become entitled to bene t from these NRTPs. These factors include the preference erosion[14] that stems from both the greater liberalization [15] of most favoured nations (MFN) tariffs (in particular since the creation of the WTO) and the end of multi-bre agreement (e.g., Inama, 2003;Klasen et al, 2021;Low et al, 2009;Persson, 2015b); domestic economic policies, including trade policies [16] and the real exchange rate policies [17]; the limited supply response capacity of bene ciary countries (e.g., Gradeva and Martínez-Zarzoso 2016;Low et al, 2009;Prowse, 2010;Yannopoulos, 1986Yannopoulos, , 1987; the inadequate product coverage (e.g., Low et al, 2009;Persson, 2015b); the existence of restrictive rules of origin as well as other compliance costs by the bene ciary countries when claiming a NRTP (e.g., Brenton and Özden 2009;Gitli, 1995;Persson, 2015b;WTO, 2019); and the lack of certainty or stability of the improved market access brought about by the NRTP (e.g., Hakobyan, 2020;Persson, 2015b). For example, concerning the rules of origin, the literature has shown that restrictive 'preferential' rules of origin can constrain the bene ts of tariff preference margins (e.g., Cadot et al, 2014) by leading to a misallocation of resources (e.g., Falvey and Reed, 1998;Mattoo et al, 2003) and ultimately undermining the utilization of NRTPs (Hakobyan, 2015;Herz and Wagner, 2011;Inama, 2003;Sytsma, 2021;WTO, 2019).…”
Section: Theoretical Discussionmentioning
confidence: 99%
“…Additionally, many factors can hinder the utilization of NRTPs once bene ciary countries become entitled to bene t from these NRTPs. These factors include the preference erosion[14] that stems from both the greater liberalization [15] of most favoured nations (MFN) tariffs (in particular since the creation of the WTO) and the end of multi-bre agreement (e.g., Inama, 2003;Klasen et al, 2021;Low et al, 2009;Persson, 2015b); domestic economic policies, including trade policies [16] and the real exchange rate policies [17]; the limited supply response capacity of bene ciary countries (e.g., Gradeva and Martínez-Zarzoso 2016;Low et al, 2009;Prowse, 2010;Yannopoulos, 1986Yannopoulos, , 1987; the inadequate product coverage (e.g., Low et al, 2009;Persson, 2015b); the existence of restrictive rules of origin as well as other compliance costs by the bene ciary countries when claiming a NRTP (e.g., Brenton and Özden 2009;Gitli, 1995;Persson, 2015b;WTO, 2019); and the lack of certainty or stability of the improved market access brought about by the NRTP (e.g., Hakobyan, 2020;Persson, 2015b). For example, concerning the rules of origin, the literature has shown that restrictive 'preferential' rules of origin can constrain the bene ts of tariff preference margins (e.g., Cadot et al, 2014) by leading to a misallocation of resources (e.g., Falvey and Reed, 1998;Mattoo et al, 2003) and ultimately undermining the utilization of NRTPs (Hakobyan, 2015;Herz and Wagner, 2011;Inama, 2003;Sytsma, 2021;WTO, 2019).…”
Section: Theoretical Discussionmentioning
confidence: 99%
“…• Access to capital 10 (Shehrawat, 2006;Dao, 2016;Mashimba & Kühl, 2014;Breisinger et al, 2009;Munyi, 2020;Thindisa & Urban, 2018) 19.3 Ahmed et al, 2014;Shehrawat, 2006;Sanida et al, 2016;Shifa, 2015;Klasen et al, 2021;Martin, 2019;Panda, 2015;Ruslan, 2018;Hawkes, 2005;Watanabe et al, 2009;Mashimba & Kühl, 2014;Rae & Josling, 2003;Osei-Amponsah, 2020;Breisinger et al, 2009;De Vries et al, 2015;Ahmad, 2020;Venkatesh et al, 2017) 54.8…”
Section: Future Researchunclassified
“…International trade and exports of agro-based manufactured products 11 (Dao, 2016;Kodama, 2017;Klasen et al, 2021;Hawkes, 2005;Sanida et al, 2016;Wattanapruttipaisan, 2003;Shifa, 2015;Rae & Josling, 2003) 3…”
Section: Future Researchmentioning
confidence: 99%
“…[16] Demaria (2017, 2020); Fernandes et al (2019); Herz and Wagner (2011); Klasen et al (2021); Low et al (2009); and Tobin (2018).…”
Section: Brief Literature Review On the Effect Of Nrtps On Export Earnings And Export Diversi Cationmentioning
confidence: 99%
“…Preference erosion has become an issue of serious concern since the inception of the WTO. It has resulted in lower export opportunities for bene ciary countries of NRTPs, in particular for the poorest among them, i.e., LDCs (e.g., Klasen et al, 2021) and can limit the capacity of these countries to diversify their export product baskets towards sophisticated goods. Low et al (2009) have estimated that MFN tariffs cut on non-agricultural products by the QUAD economies plus Australia would lead to a signi cant erosion of preferences for LDCs as well as for a set of countries [23].…”
Section: Issue Of Preference Erosion and Product Coverage Of Nrtpsmentioning
confidence: 99%